2019
DOI: 10.1021/acs.energyfuels.9b01716
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultrashort Hydrophobe Surfactants with Cosolvent Characters for Heavy Oil Recovery

Abstract: A new class of ultrashort hydrophobe surfactants with cosolvent characters was investigated as a sole additive to conventional polymer flooding for heavy oil recovery. No alkali was used for emulsification. The surfactants were composed of a short hydrophobe (phenol in this research) extended by propylene oxide (PO) and ethylene oxide (EO) units to achieve a sufficient level of surface activity and aqueous stability: phenol-xPO-yEO. Results are presented for the selection of ultrashort hydrophobe surfactants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The PO and EO groups affect the hydrophobicity and aqueous stability of the surfactant, respectively. Although other ultrashort hydrophobe surfactants were studied previously for improving polymer flooding by Baek et al, 2-EH– x PO– y EO surfactants are studied for the first time as a simple surfactant solution for enhancing water imbibition in fractured media in this research …”
Section: Methodsmentioning
confidence: 95%
“…The PO and EO groups affect the hydrophobicity and aqueous stability of the surfactant, respectively. Although other ultrashort hydrophobe surfactants were studied previously for improving polymer flooding by Baek et al, 2-EH– x PO– y EO surfactants are studied for the first time as a simple surfactant solution for enhancing water imbibition in fractured media in this research …”
Section: Methodsmentioning
confidence: 95%
“…Recently, short-hydrophobe surfactants were studied by several researchers. Wang et al tested a short-hydrophobe surfactant as a wettability modifier for oil recovery from fractured limestone cores . They found that 2-etheylhexanol-4PO-15EO (or 2-EH-4PO-15EO) altered the wettability of calcite surfaces from oil-wet (contact angle: 134.1°) to water-wet (contact angle: 47.1°) after 1 day.…”
Section: Introductionmentioning
confidence: 99%
“…Baek et al tested phenol-4PO-20EO for heavy oil recovery in a high-permeability glass-bead pack . They conducted water flooding, 40-cp polymer flooding, and low-tension 40-cp polymer flooding to displace a 276-cp heavy oil.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations